Development of poly(lactic acid) films with propolis as a source of active compounds: Biodegradability, physical, and functional properties. Issue 8 (21st September 2018) - Ulloa, P. A.; Vidal, J.; Lopéz de Dicastillo, C.; Rodriguez, F.; Guarda, A.; Cruz, R. M. S.; Galotto, M. J.
ABSTRACT: Active films (AFs) using poly(lactic acid) (PLA) as a polymeric matrix containing various propolis concentrations (5, 8.5, and 13%) as the active agent (AA) were developed using a casting method. The purpose was to determine the effects of the incorporation of AA on the physical properties of the films and to evaluate the antioxidant and antimicrobial activities. Tensile strength and elastic modulus of the AFs decreased relative to the control (PLA without AA). Introducing the active substances from propolis into the PLA also affected its thermal properties (glass transition). Adding AAs to the polymer generated more opacity with a green‐yellowish color compared to the control. In addition, AFs exhibited reduced water vapor permeability as the AA concentration increased. Biodegradation assay showed that the AFs degraded faster than the control. AFs exhibited antioxidant activity, which was measured as the ability to scavenge free radicals (2, 2‐diphenyl‐1‐picrylhydrazyl and 2, 2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonate)), due to the presence of bioactive compounds (phenolics). Antimicrobial activity was evaluated against Escherichia coli and showed a reduction over 4‐log cycles. Therefore, incorporation of propolis is a useful strategy for the development of active packaging with antioxidant and antimicrobial effects, which increase the shelf life of food products. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47090. Abstract :